ANALISIS PENYAJIAN LAPORAN KEUANGAN PESANTREN BERDASARKAN SAK ETAP PADA PONDOK PESANTREN ASSHOLACH PASURUAN - Fitri Rizqy Amalia; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study was to determine the process of preparing financial statements in terms of recognition, measurement, recording, disclosure and presentation at Assholach Islamic Boarding School. This research is included in this descriptive qualitative by using interviews and documentation. The results showed that Islamic Boarding Schools did not prepare financial reports in accordance with SAK ETAP for approach, assessment, recording and disclosure. Assholach Islamic Boarding School uses single entry bookkeeping to prepare its financial statements. Assholach only made one report. This is due to the lack of human resources regarding the presentation of financial statements based on SAK ETAP. Bank Indonesia and Ikatan Akuntansi Indonesia can prepare pesantren socialization regarding the recording and presentation of pesantren accounting.Keywords: financial reporting, accounting, islamic boarding school, SAK ETAP